PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP PEMAHAMAN KONSEP PADA MATERI GELOMBANG DI KELAS VIII SMP NEGERI 5 PUTUSSIBAU - Nickolaus Febryan Roni; Erwina Oktavianty; Muhammad Musa Syarif Hidayatullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Understanding scientific concepts is an essential component in physics learning, yet many students still experience difficulties in comprehending abstract concepts, particularly in wave material. This study aims to determine the effect of the discovery learning model on students’ conceptual understanding in wave material in grade VIII of SMP Negeri 5 Putussibau. The research employed a quasi-experimental method using a non-equivalent control group design involving an experimental class and a control class. The experimental class was taught using the discovery learning model, while the control class used the direct instruction model. Data were collected through pre-test and post-test instruments designed to measure students’ conceptual understanding. The results of the study indicate that students taught using the discovery learning model experienced a greater improvement in conceptual understanding compared to those taught using direct instruction. This improvement is reflected in the higher N-Gain value obtained by the experimental class. The findings suggest that discovery learning encourages students to actively explore, analyze, and construct their own understanding of concepts through observation and discussion. Therefore, the discovery learning model can be considered an effective instructional strategy to enhance students’ conceptual understanding in physics learning, particularly in topics that require deeper conceptual comprehension such as wave material.